Analisa Perbandingan Hasil Pohon Keputusan Dengan Gain Ratio, Information Gain, Dan Gini Index Pada Pemasaran Produk Herbal di CV. Al-Ghuroba - Asmara, Husnul Maula; , Fatah Yasin Al Irsyadi, S.T., M.T (2016)
CV.Al-Ghuroba 'is a company engaged in the production and distribution of natural herbal products, located in Sukoharjo regency, Central Java province. CV.Al-Ghuroba 'has transactional data very much and accumulate over time, it would be very useful if the data is processed and will generate strategic information for the company. This study aims to help companies in taking an appropriate decision by comparing the results of the decision tree to Gain Ratio, Information Gain, and Gini Index .With data mining technology, transaction data will be used as a source of strategic information to determine the company's marketing strategy. The data mining method used in the decision to use decision tree method by comparing the results of the decision tree to Gain Ratio, Information Gain, and Gini Index. Attributes are used for data mining process consists of supplier attributes, attribute categories, attributes gender, attributes the city, and the price attributes. The results showed that the variables that most influence on the sales trend is variable suppliers. viewed from the Gini Index precission method better because it has a higher value than the other methods that have precission value of 77.41%. However, if viewed from the Recall and Accuracy Method of Information Gain and Gain Ratio better than the Gini index for value Recall and Accuracy equal and higher than the Gini Index method.